Covid-19 as an opportunity for more sustainable tourism : a realistic expectation? - Lena Marie Heinze 1994- (2020)
The pandemic outbreak of Covid-19 in 2020 had major implications for the tourism industry, with travel reduced to the bare minimum and tourism demand at an all-time low. This led to much speculation about the effects of the crisis on sustainability and whether this can be a turning point for the tourism industry to become more sustainable. This study investigates the effect of the Covid-19 pandemic outbreak on sustainability in rural tourism firms with a multi-method approach. Qualitative results from interviews with business owners/managers and quantitative results from survey responses of rural tourism businesses in Iceland were analysed. The study shows a significant increase between sustainability performance in 2019 and planned sustainability performance in 2021, showing an intent of businesses to behave more sustainably. The outlook on sustainability after the pandemic outbreak of Covid-19 depends on the future behaviour of the pandemic, future demand for tourism and policy. Implications for managers show an urgency to utilise the current phase of openness to organisational change, capture and reflect on learnings from the crisis and turn them into strategy and actions to build more resilient and sustainable businesses. On an institutional level, it is important to react in a time sensitive manner to design policy specific to outcomes of Covid-19 that supports and incentivises more sustainable business behaviour and addresses sustainability challenges in the industry to create lasting changes in tourism sustainability.